Tissue Engineering of Ureteral Grafts: Preparation of Biocompatible Crosslinked Ureteral Scaffolds of Porcine Origin - Koch, Holger; Hammer, Niels; Ossmann, Susann; Schierle, Katrin; Sack, Ulrich; Hofmann, Jörg; Wecks, Mike; Boldt, Andreas (Frontiers in Bioengineering and Biotechnology, 2015)
The surgical reconstruction of ureteric defects is often associated with postoperative complications and requires additional medical care. Decellularized ureters originating from porcine donors could represent an alternative therapy. Our aim was to investigate the possibility of manufacturing decellularized ureters, the characteristics of the extracellular matrix (ECM) and the biocompatibility of these grafts in vitro / in vivo after treatment with different crosslinking agents. To achieve these goals, native ureters were obtained from pigs and decellularized. The success of decellularization and the extracellular matrix (ECM) composition were characterized by (immuno)histological staining methods and an DNA-assay. In vitro: scaffolds were crosslinked either with carbodiimide (CDI), genipin (GP), glutaraldehyde (GA), left chemically untreated or were lyophilized. Scaffolds in each group were reseeded with Caco2, LS48, 3T3 cells or native rat smooth muscle cells (SMC). After 2 weeks, the number of ingrown cells was quantified. In vivo: crosslinked scaffolds were implanted subcutaneously into rats and the type of infiltrating cells were determined after 1, 9 and 30 days. After decellularization, scaffold morphology and composition of ECM were maintained, all cellular components were removed, DNA destroyed and strongly reduced. In vitro: GP and CDI scaffolds revealed a higher number of ingrown 3T3 and SMC cells, as compared to untreated scaffolds. In vivo: at day 30, implants were predominantly infiltrated by fibroblasts and M2 anti-inflammatory macrophages. A maximum of MMP3 was observed in the CDI group at day 30. TIMP1 was below the detection limit. In this study, we demonstrated the potential of decellularization to create biocompatible porcine ureteric grafts, whereas a CDI-crosslink may facilitate the remodeling process. The use of decellularized ureteric grafts may represent a novel therapeutic method in reconstruction of ureteric defects.